Outcomes after salvage radiation for local and regional recurrence of endometrial cancer - Chunmei Li; Jiayin Wu; Gajincuo Du; Linlin Chen; Haoting Shi; Rong Cai (Holistic Integrative Oncology)
Abstract Purpose We aimed to report the effectiveness and toxicity of salvage radiation for postoperative endometrial cancer (EC). Methods Between 2017 and 2022, 17 post-hysterectomy EC patients with loco-regional recurrence received salvage radiation were enrolled. The survival outcomes were progression-free survival (PFS), local control (LC), distant metastasis and overall survival (OS). The toxicity was analyzed according to the radiation dose. Results Among these participants, the most common relapse site was vaginal apex (N = 10 [58.8%]). Salvage radiation contained external beam radiotherapy (EBRT) alone (N = 9 [52.9%]), vaginal brachytherapy alone (N = 2 [11.8%]) and combined (N = 6 [35.3%]). Median EQD2_10 was 44.25 Gy (interquartile range [IQR], 44.25–44.25) and cumulative EQD2_10 was 44.25 Gy (IQR, 44.25—68.25). After the median follow-up time of 45 months (ranged 3–64), the 4-year PFS, LC, distant metastasis and OS rate was 54.1% (95% CI,31.7%—92.2%), 61.1% (95% CI,38.7%—96.4%), 82.4% (95% CI,61.8%—100.0%) and 86.5% (95% CI,70.7% -100.0%), respectively. Concurrent chemotherapy demonstrated a trend in protective effect on metastasis (hazard ratio [HR] 0.71 [95% CI, 0.06—8.0]), instead of local control (HR 5.69 [95% CI, 0.62—52]). There was no grade ≥ 3 acute or late rectosigmoid or bladder toxicities. Higher pelvic dose was found among whom experienced myelosuppression (P = 0.03). Conclusion Salvage radiation for loco-regional recurrence EC demonstrated promising LC and OS, with acceptable toxicity. More extensive research is needed to explore its efficacy and safety in a larger cohort.